2017
DOI: 10.1128/iai.00303-17
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Probiotics Targeting Clostridium difficile through Precursor-Directed Antimicrobial Biosynthesis

Abstract: Integration of antibiotic and probiotic therapy has the potential to lessen the public health burden of antimicrobial-associated diseases. infection (CDI) represents an important example where the rational design of next-generation probiotics is being actively pursued to prevent disease recurrence. Because intrinsic resistance to clinically relevant antibiotics used to treat CDI (vancomycin, metronidazole, and fidaxomicin) is a desired trait in such probiotic species, we screened several bacteria and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 78 publications
(90 reference statements)
2
62
1
2
Order By: Relevance
“…; Spinler et al . ; Najarian et al . ) and prevention of C. difficile colonization via competitive exclusion (Dicks et al .…”
Section: Resultsmentioning
confidence: 99%
“…; Spinler et al . ; Najarian et al . ) and prevention of C. difficile colonization via competitive exclusion (Dicks et al .…”
Section: Resultsmentioning
confidence: 99%
“…Another researcher found that only co‐delivery of L. reuteri with glycerol could effectively fight against C. difficile colonization. Treatment with either glycerol or L. reuteri could not efficaciously inhibit outgrowth of C. difficile (Spinler et al, ).…”
Section: Antimicrobial Activity Of Probioticsmentioning
confidence: 99%
“…By analyzing the microbiome between healthy and diseased individuals, a variety of bacteria have been found to correlate with diseases . Meanwhile, some bacteria were found being more abundant in the healthy population and might have potential to be used as probiotics . These newly discovered bacteria, originated from the microbiome‐based analysis, could be referred to as the “next‐generation probiotics.” Indeed, the amelioration of culture system, including the development of bioreactors, formulation of new isolation protocol, and modification of culture media, also contribute to the discovery of next‐generation probiotics.…”
Section: Microbiome‐based Anti‐obesity Potential: Next‐generation Promentioning
confidence: 99%
“…Meanwhile, some bacteria were found being more abundant in the healthy population and might have potential to be used as probiotics . These newly discovered bacteria, originated from the microbiome‐based analysis, could be referred to as the “next‐generation probiotics.” Indeed, the amelioration of culture system, including the development of bioreactors, formulation of new isolation protocol, and modification of culture media, also contribute to the discovery of next‐generation probiotics. The development of metabolomics, an advanced technique for analyzing both the composition of metabolites from microbes and host, allows the researchers to establish the potential link between microbes and host, and provides the possible mechanisms for further investigation .…”
Section: Microbiome‐based Anti‐obesity Potential: Next‐generation Promentioning
confidence: 99%
See 1 more Smart Citation